Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

ChicaAmbitio

  • 3 years ago

@hoblos : Solve 6(x + 1) - 4 = 3x + 2.

  • This Question is Closed
  1. hoblos
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 1

    6(x + 1) - 4 = 3x + 2 6x + 6 -4 = 3x +2 6x +2 = 3x +2 3x =0 so x = 0

  2. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy